Design and performance of an additively manufactured high-Si transformer core. (September 2020) - Plotkowski, A.; Carver, K.; List, F.; Pries, J.; Li, Z.; Rossy, A. Marques; Leonard, D.
Abstract: Additive manufacturing (AM) of functional alloys has become a promising area of research for the development of novel devices with complex geometric features that cannot be manufactured using conventional methods. In this work, we investigate the additive manufacturing of Fe3Si and Fe6Si benchtop scale transformer cores. A novel design inspired by a Hilbert curve was developed to exploit the geometric complexity of AM, and cores of each alloy were successfully printed, heat treated, machined, pickled, and assembled. The microstructure and magnetic performance of the cores were characterized and compared to additively manufactured components with simpler square cross-sections as well as to conventionally laminated non-oriented electrical steel sheet. The AM cores showed performance roughly comparable or better than the conventional non-oriented sheet, but higher power losses than Goss oriented steel. The increased Si content of the Fe6Si alloy resulted in a significant reduction in core losses. The transformer cores had higher losses than the similarly manufactured simple cross-sections, which was attributed to defects in fabrication and assembly that resulted in air gaps between the transformer legs. The performance was also rationalized relative to nanoscale carbide and oxide inclusions. Graphical abstract: Unlabelled Image Highlights: Design and fabrication of additively manufactured Fe3Si and Fe6Si transformer cores. Characterization of microstructure and magnetic properties. AM of high-Si alloy provide a significant reduction in AC power losses. Discussion of influence of processing and chemistry on performance and comparison to previous results in the literature.